American Think Tanks on Muslims: An Overview of the Activities of Rand Corporation (Al-Qamar, 2018)
This paper endeavors to give an overview of the attitude and activities of American Think Tank “Rand Corporation” towards the Muslim Ummah. It finds that Rand Corporation has an agenda explicitly against the interests and rights of the Muslims. About its activities it is clearly said that assisting secularists and modernists should be an important part of US foreign policy about the Muslim world.  It should be US priority to provide support for their educational and cultural activities. Special attention should be given to the reform of madrassas and mosques. The curriculum of the madrassas should be revised according to modern requirements. Modernist scholars should be given full access to print and electronic media. Their ideas should be incorporate into the curriculum of Islamic countries. In short Rand Corporation suggests and promotes divisions between different Muslim sects and countries for US interests.
Keywords: US Think Tanks; Rand; activities; Muslims